1966
DOI: 10.1136/bmj.1.5494.1016
|View full text |Cite
|
Sign up to set email alerts
|

Average Normal Values for the Forced Expiratory Volume in White Caucasian Males

Abstract: Bronchodilator Therapy-Hoffbrand et al.be the preferable instrument for following changes in airway resistance in consulting-room and bedside practice. SummaryA comparison has been made using lung-function tests of three proprietary bronchodilator preparations given by dry metered aerosol to 24 patients with asthma and chronic bronchitis.Isoprenaline sulphate (1.20 mg.) was found to be the most effective preparation for the first 30 to 45 minutes after inhalation. Though orciprenaline (2.25 mg.) was less effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 12 publications
4
26
0
Order By: Relevance
“…All the measured lung function indices declined with age, as expected, as the functional efficiency of the lung deteriorates with age 18 . The present study with relatively low cumulative silica exposure has shown no significant effect, as obtained in multiple regression analysis, of increasing total cumulative exposure to respirable dust in the mine on the mean FEV 1 (% predicted), mean FEV 1 /FVC ratio and mean FVC (%predicted), but there is a significant increasing effect of total cumulative respirable dust exposure and the combined effect of smoking and total cumulative respirable dust exposure on mean FEF 25-75% (% predicted) (p=0.011 and p=0.009 respectively), while a significant increase in mean FVC was observed with smoking (p=0.020).…”
Section: Lung Function Testssupporting
confidence: 77%
“…All the measured lung function indices declined with age, as expected, as the functional efficiency of the lung deteriorates with age 18 . The present study with relatively low cumulative silica exposure has shown no significant effect, as obtained in multiple regression analysis, of increasing total cumulative exposure to respirable dust in the mine on the mean FEV 1 (% predicted), mean FEV 1 /FVC ratio and mean FVC (%predicted), but there is a significant increasing effect of total cumulative respirable dust exposure and the combined effect of smoking and total cumulative respirable dust exposure on mean FEF 25-75% (% predicted) (p=0.011 and p=0.009 respectively), while a significant increase in mean FVC was observed with smoking (p=0.020).…”
Section: Lung Function Testssupporting
confidence: 77%
“…This increase however was only empirical as there was no statistical difference between the phases of the menstrual cycle studied (figure 4). Anthropometric parameters such as age, sex, weight and height have also been documented to affect pulmonary function (Alakija et al,1990;Cotes et al,1966;Jain et al,1983) The difference in body mass indices of both groups studied (figure 5) was not statistically significant (p>0.05). Consequently, the progesterone dominance in the luteal phase is accountable for the relative enrichment in pulmonary function in this phase compared to the menstrual phase.…”
Section: Resultsmentioning
confidence: 93%
“…FEV1.0 is also defined as the maximum volume which can be expired in the first second of forced expiration after maximal inspiration (Committee on Pulmonary Physiology, A. C. C. P., 1963). However, it is not clearly defined whether the mean or the maximum value of the repeated measurements should be taken as the actual ventilatory capacity for assessment (COTES et al ., 1966;DEKROON et al, 1964;DENSEN et al, 1966 ;FERRIS et al, 1965;GILSON and HUGH-JONES, 1949 ;JOUASSET, 1960;MILLS, 1949).…”
Section: Discussionmentioning
confidence: 99%